KECERNAAN INVITRO FERMENTASI PUCUK TEBU MENGGUNAKAN UREA DAN MOLASES - Ay, Apriyanto Nyali; Iskandar, Ahmad; Marhaeniyanto, Eko (Universitas Tribhuwana Tunggadewi, 2018)
This research was conducted with the aim of knowing the dry matter content, organic matter, dry matter and organic matter digestibility. The study was conducted in the Central Laboratory of Tribhuwana Tunggadewi University Malang for the stages of fermentation of sugarcane shoots using urea and molasses. For the second stage was the analysis of dry matter, digestibility of dry matter and organic matter, digestibility of organic matter for in vitro experiments using the Tilley and Terry method (1963) in the Animal Husbandry Nutrition and Food Laboratory, Malang. The research materials were sugar cane shoots, urea and molasses. The experimental method using a completely randomized design (CRD). Consists of 4 treatments and 6 replications. Each treatment unit was carried out in in vitro tests in duplicate. The description of treatment were P0: Cane shoots (Control), P1: Sugarcane shoots + Urea 5%, P2: Sugarcane shoots + 10% Molasses, P3: Sugarcane shoots + 5% Urea + 10% Molasses. The results showed a very significant effect (P